2020
DOI: 10.1007/s00246-020-02433-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ventricular Function After Bidirectional Cavopulmonary Connection: Who Is at Risk?

Abstract: Decline of single ventricle systolic function after bidirectional cavopulmonary connection (BDCPC) is thought to be a transient phenomenon. We analyzed ventricular function after BDCPC according to ventricular morphology and correlated this evolution to long-term prognosis. A review from Mayo Clinic databases was performed. Visually estimated ejection fraction (EF) was reported from pre-BDCPC to pre-Fontan procedure. The last cardiovascular update was collected to assess longterm prognosis. A freedom from majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…This temporarily impaired ventricular performance is a known phenomenon that has previously been reported for several CHD diagnoses [16]. Recently, Vincenti et al reported that ventricular impairment-assessed by ejection fraction obtained during cardiac catheterization-at hospital discharge and up to the months following PCPC was more severe for patients with a dominant right ventricle compared to those with a dominant left ventricle [17]. Our present study confirms this finding.…”
Section: Discussionsupporting
confidence: 90%
“…This temporarily impaired ventricular performance is a known phenomenon that has previously been reported for several CHD diagnoses [16]. Recently, Vincenti et al reported that ventricular impairment-assessed by ejection fraction obtained during cardiac catheterization-at hospital discharge and up to the months following PCPC was more severe for patients with a dominant right ventricle compared to those with a dominant left ventricle [17]. Our present study confirms this finding.…”
Section: Discussionsupporting
confidence: 90%
“…This trial enrolled patients with normal RVEF at baseline. Consistent with previous natural history studies, RVEF drops following the stage II BDCPA due to loading condition alterations, but remains in the normal range (41). It is estimated that∼10% of children develop frank RV failure and require transplantation or die, with less than half of the children having transplant free survival to 15 years of age (42).…”
Section: Discussionsupporting
confidence: 89%
“…The RVs had a decreased mean EF after bidirectional cavopulmonary connection (BDCPC) compared with single morphologic LVs, which remained stable 5,6,36 . Moreover, Vincenti et al recently published sim ilar results, especially in the HLHS population subset 37 .…”
Section: Discussionmentioning
confidence: 95%